Preliminary mango selection - Ascenso, J. Crespo; Milheiro, A. Vaz; Mota, M. Isabel; Cabral, M. (Pesquisa Agropecuaria Brasileira, 2014)
Studies on evaluation of 19 mango selections and cultivars are reported. Data are presented on yields and fruit characteristics. Observations were made and data taken on color, size and shape, weight and volume, embryony, peel thickness and adherence, flavor, texture and fiber content, juice, soluble solids and sugars, acidity, pH, and ratio of soluble solids to acidity. The following five varieties were selected as most desirable: 'Afonsa Pairi', 'Extrema' and 'Zoologia' for the fresh market, 'Monserrate' for late season of maturity and 'Sabre' because it is polyembryonic and comes true from seed. A brief description is given of these varieties.